Bridging a transnational mother-daughter's relationship through a memoir - Widyarini Susilo Putri; Sinead McDermott (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
Bridging the past and present in a family is challenging, particularly if they grow up in a different culture. The hassle of life occupies most people's minds, which leads to abandoning one of the most fundamental kinships, the mother-daughter relationship. This phenomenon appears in a literary work written by Amy Tan entitledÂ The Bonesetter's Daughter, where the protagonist acts apathetic toward her mother's willingness to preserve their family's lineage through a handwritten memoir.Reading the literary work through the lens of Memory Studies helps to understand the mother's unpleasant to hostile behaviours in the protagonist's upbringing; besides her harsh past that caused it, the daughter's obliviousness toward her mother's wishes in getting to know about her real grandmother and the history of their family heightened her disappointment. As an Asian, family ties serve as a vital source of identity and safeguard against life's challenges, and the bond is severed more due to the different communication styles.Realising the importance of reading the forgotten memoir written by her mother became the turning point of their relationship. By willingly reading the mother's memory, finally, the daughter creates a long-wished family connection.Â